2019
DOI: 10.1016/j.enzmictec.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of enzyme adsorption in the enzymatic degradation of an aliphatic polyester

Abstract: The enzyme catalyzed degradation of poly(3-hydroxybutyrate) (PHB) is a two-step process consisting of the adsorption of the enzyme on the surface of a PHB substrate and the cleavage of ester bonds. A deactivated enzyme was prepared by point mutagenesis to separate the two steps from each other. Measurements carried out with active and inactive enzymes on PHB particles proved that mutagenesis was successful and the modified enzyme did not catalyze degradation. Based on the Michaelis-Menten approach a kinetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It is possible that the binding of enzymes on the sensor would contribute to the quenching in the fluorescence change (reaction ). The adsorption of proteins on nanoparticles is reported to occur in the time scale of minutes, , whose time scale is similar to the quenching in fluorescence observed in our experiments. However, we have compared the results of turbidity and fluorescence change (Figure b) and found that the turbidity change occurs immediately after enzyme addition.…”
Section: Resultssupporting
confidence: 85%
“…It is possible that the binding of enzymes on the sensor would contribute to the quenching in the fluorescence change (reaction ). The adsorption of proteins on nanoparticles is reported to occur in the time scale of minutes, , whose time scale is similar to the quenching in fluorescence observed in our experiments. However, we have compared the results of turbidity and fluorescence change (Figure b) and found that the turbidity change occurs immediately after enzyme addition.…”
Section: Resultssupporting
confidence: 85%
“…[19][20][21][22][23] Many methods of immobilization are described and used in the literature to circumvent the possible instability problems of the enzymes as well as to optimize the various applications. In recent years, the empirical use of these immobilization techniques (for example, covalent bonding, 24 physical adsorption, 25 ionic adsorption, 26 crosslinking, 27 encapsulation, 28 etc) and their influences on the specificity, activity and stability of the enzymatic molecules, as well as the usability of the biocatalysts for application-related [29][30][31] reactions. 29,[32][33][34][35] These immobilized enzymes, bound to the solid supports, can simply be removed from the reaction mixture.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…A very important aspect of this family of enzymes is that they incorporate a substrate binding domain (SBD), which adsorbs on the polymer surface. Hence, hydrolysis by PHB-depolymerases is a two-step reaction, beginning with adsorption, which has its own kinetics and can be a rate-limiting step ( Polyák et al, 2019 ). It should be noted that the SBDs do not show exclusive affinity for the polymers the enzyme can actually hydrolyze ( Kasuya et al, 1996 ).…”
Section: Microbial and Enzymatic Degradation Of Plasticsmentioning
confidence: 99%